A revision of Sabella, Bispira and Stylomma (Polychaeta: Sabellidae) - Knight-Jones, Phyllis; Perkins, Thomas H. (Zoological Journal of the Linnean Society, London, 1998)
Sabella is rediagnosed to include only species that have spiralled fascicles of abdominal chaetae, first thoracic shield with straight anterior border and radioles that lack composite eyes and flanges. Spirographis spallanzanii is synonymous with Sabella penicillus. The type of the genus is discussed and a neotype designated. The only other species retained in Sabella are S. pavonina and S. discifera (=Branchiomma linaresi, once misplaced in Megalomma, but abdominal fascicles of Megalomma form transverse rows). Most species formerly placed in Sabella are transferred to Bispira, having C-shaped fascicles of abdominal chaetae, first thoracic shield with a "W"-shaped anterior border and, in most species, radioles with paired composite eyes and flanges. Bispira, with B. volutacornis as the type species, is rediagnosed to include B. crassicornis, B. fabricii, B. melanostigma, B. tricyclia, B. viola, B. manicata, B. porifera, B. mariae, B. elegans, B. brunnea, B. guinensis, B. secusolutus, B. wireni, B. oatesiana, B. spirobranchia, B. pacifica, B. monroi, and B. turneri, many of which are described fully for the first time. Only five of these form bispiral crowns (bispirality is useful only specifically and occurs in other genera) and one, B. tricyclia, has a unispiral crown. Sabella palmata Quatrefages, the type of Stylomma is redescribed and its synonyms discussed. This genus has abdominal fascicles like those of Bispira, but radiolar eyes like those of Megalomma. The relative advantages of chaetal arrangement and eye position are discussed.
World Polychaeta Database (WPolyDb)